A 30mV input battery-less power management system - Jim Hui Yap; Yan Chiew Wong (Institute of Advanced Engineering and Science, 2019)
This paper presents a fully-integrated on chip battery-less power management system through energy harvesting circuit developed in a 130nm CMOS process. A 30mV input voltage from a TEG is able to be boosted by the proposed Complementary Metal-Oxide-Semiconductor (CMOS) voltage booster and a dynamic closed loop power management to a regulated 1.2V. Waste body heat is harvested through Thermoelectric energy harvesting to power up low power devices such as Wireless Body Area Network. A significant finding where 1 Degree Celsius thermal difference produces a minimum 30mV is able to be boosted to 1.2V. Discontinuous Conduction Mode (DCM) digital control oscillator is the key component for the gate control of the proposed voltage booster. Radio Frequency (RF) rectifier is utilized to act as a start-up mechanism for voltage booster and power up the low voltage closed loop power management circuit. The digitally control oscillator and comparator are able to operate at low voltage 600mV which are powered up by a RF rectifier, and thus to kick-start the voltage booster.